Branding in Health Tourism and Bursa’s Potential to become a Brand City in Health Tourism - BERKÜN , Sanem (Journal of Ecohumanism, 2024)
Objective: With this study, the potential of Bursa to become a brand city in health tourism has been evaluated and suggestions have been developed to increase success in this process. Theoretical Framework: Health tourism, which has become increasingly important in recent years due to reasons such as unplanned urbanization, increasing environmental problems, and aging of the population, refers to travel between cities or countries for treatment and holiday purposes. Health tourism can be performed in three different ways: medical tourism, thermal springs tourism or elderly and disabled care tourism. Increasing of the health tourism revenues direct countries to develop by investing in this field. Various cities with suitable potential add health tourism to their branding strategies. Prominent countries within this field are India, Singapore, Malaysia, South Africa and Türkiye. Türkiye stands out with its geopolitical location, natural beauties, rich underground and surface resources as well as its capacity to provide quality and cheap healthcare services. In terms of health tourism, Bursa is among the prominent cities of Türkiye with its diversity of medical facilities, healing water resources and transportation opportunities. Method: In the study, phenomenology method which is utilized in literature review and qualitative research is used and in-depth interviews with local tourists who came to Bursa for health tourism have been conducted to find out how Bursa is received in terms of health tourism. Result and Implications: In the study using qualitative research method, the findings obtained through in-depth interviews showed that Bursa is a preferred city in terms of health tourism. Particularly service quality and diversity, low cost, ease of transportation and the abundance of things to do in Bursa are effective in the satisfaction of visitors who come to Bursa for health tourism. On the other hand; the fact that there are too many foreign tourists in hotels, the fewer number of package tours to Bursa, that Bursa is crowded and the lack of railway transportation to Bursa are the disliked aspects of Bursa regarding health tourism.